Synthesis, Cytotoxic and Antihyperlipidemic Activities of Some New coumarinyl 4-Thiazolidinone Derivatives - Bhat, Katte Ishwar; Kumar, Abhishek; Kumar, Pankaj (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Despite tremendous advancements both in early diagnosis and approaches to treatment, cancer still remains an unconquered problem. The development of new chemotherapeutic agents for the treatment of cancer with fewer side effects is an important goal for medicinal chemists. Hyperlipidemia is a worth-mentioning risk factor in quickly expanding cardiovascular diseases, including myocardial infarction and, furthermore, in stroke. Hence, there is a need to develop new cytotoxic and antihyperlipidemic drugs. Materials and Methods: In the present study, a series of new substituted 2-(4-hydroxy-2-oxo-2H-chromen-3-yl)-2-methyl-3-phenylthiazolidin-4-one (TKA1-TKA13) were synthesized by reacting various 4-hydroxy-3-(1-(phenylimino) ethyl)-2H-chromen-2-one with thioglycollic acid. The intermediate 4-hydroxy-3-(1-(phenylimino) ethyl)-2H-chromen-2-one (SKA1-SKA13) were synthesized by reacting 4-hydroxyl coumarin with various substituted anilines in alcohol medium. All the newly synthesized compounds were assigned on the basis of IR, 1H NMR and mass spectral data. Results: The newly synthesized compounds were evaluated for in-vitro cytotoxic activity using Methyl Thiazolyl Tetrazolium (MTT) assay and in-vitro antihyperlipidemic activity by HMG-CoA reductase assay. Compound TKA12 possess potent cytotoxic activity on lung adenocarcinoma cells in a concentration dependent manner compared to the standard cisplatin. Most of the compounds showed potent antihyperlipidemic activity comparable with that of the standard pravastatin. Conclusion: The in-vitro results suggest that most of the compounds may be a promising antihyperlipidemic molecules and compound TKA12 showed potent cytotoxic activity which can be further determined by in vivo studies.
Keywords: Coumarins; Schiff bases; 4-Thiazolidinones; Cytotoxic activity; Antihyperlipidemic activity